The Internal Conflict of the Character Jana in the Film “The Sand Castle” by Matty Brown - Sapta Adi Nugraha; Muhammad Rosyid Ridho; Muhammad Abdul Halim (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
he film Dari Gelombang Istana Pasir by Matty Brown through a literary psychology approach using Abraham Maslow's hierarchy of needs theory. The inner conflict is analyzed based on Maslow's five basic needs, namely physiological needs, security, love and belonging, self-esteem, and self-actualization. The method used is descriptive qualitative with listening and recording techniques, as well as content analysis of scenes and dialogues that show the inner dynamics of the characters. The results show that the inner conflict experienced by Jana arises from the pressure of extreme situations faced, such as limited basic needs, insecurity, alienation, loss of appreciation, to a strong desire to express human values through real action. This inner conflict shows how the character struggles between fulfilling personal needs and facing a limiting reality, thus enriching the understanding of character depth and psychological dynamics in film works. This research is expected to contribute to the study of literary psychology, especially in understanding the representation of characters' inner conflicts in the medium of film as a reflection of human life.